Reclaiming Narratives: Feminist Consciousness in Literature (International Journal of Food and Nutritional Sciences, 2022)
This research article explores the concept of feminist consciousness in literature and its role in reclaiming narratives. Feminist consciousness refers to the heightened awareness and critical understanding of gender inequalities and the oppression of women. Through the analysis of various literary works, this article highlights how feminist consciousness has influenced the creation and interpretation of literature, empowering women and challenging dominant patriarchal narratives. By reclaiming narratives, women writers and readers contribute to the feminist movement, reshaping societal perceptions, and promoting gender equality. The article examines the historical context of feminist consciousness in literature, its key characteristics, and the transformative potential it holds for individuals and society at large.